EIGHTH-GRADE STUDENTS’ SPEAKING ANXIETY IN JUNIOR HIGH SCHOOL - Meyshen Meyriza; Amalia Hasanah; Deta Desvitasari (Language and Educational Journal, 2024)
This study aimed to find out the description of the students’ speaking anxiety and to find out the factors that influence the students’ speaking anxiety. The researcher used a mixed method to obtain the data. For a quantitative sample, the researcher involved 80 students in the eighth grade of SMP Lematang Lestari. In collecting the data, the researcher used the PSCAS questionnaire instrument from Yaikhong and Usaha (2012) to obtain quantitative data and interviews to obtain qualitative data. From the results of the questionnaire, the anxiety level category was determined to be 3 categories, namely high (7.5%), medium (65%), and low (27.5%) anxiety level. The researcher used a homogeneous sampling approach to take samples. After that, for a qualitative sample, six students who had a high level of speaking anxiety were selected to be interviewed to find out the factors that influence students’ speaking anxiety. To analyze quantitative data, the researcher used descriptive statistics and to analyze qualitative data the researcher used thematic analysis. In conclusion, the results of the study show that the description of students’ speaking anxiety at SMP Lematang Lestari Muara Enim is mostly at a medium level of anxiety, namely 65%. Furthermore, after identifying the results of the interviews, from the things that were felt by the students, the researcher then drew 3 themes that became factors that influenced the eighth-grade students’ speaking anxiety at SMP Lematang Lestari Muara Enim, namely communication apprehension, test anxiety, and fear of negative evaluation